2021
DOI: 10.3390/microorganisms9081654
|View full text |Cite
|
Sign up to set email alerts
|

Taxogenomic and Metabolic Insights into Marinobacterium ramblicola sp. nov., a New Slightly Halophilic Bacterium Isolated from Rambla Salada, Murcia

Abstract: A Gram-negative, motile, rod-shaped bacteria, designated D7T, was isolated by using the dilution-to-extinction method, from a soil sample taken from Rambla Salada (Murcia, Spain). Growth of strain D7T was observed at 15–40 °C (optimum, 37 °C), pH 5–9 (optimum, 7) and 0–7.5% (w/v) NaCl (optimum, 3%). It is facultatively anaerobic. Phylogenetic analysis based on 16S rRNA gene sequence showed it belongs to the genus Marinobacterium. The in silico DDH and ANI against closest Marinobacterium relatives support its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Important inter-individual variation in the composition of bacterial communities among fishes of the same species has also been previously reported (Arias et al, 2019;Boutin et al, 2014). The detection of the genus Photobacterium in sea fish with relative abundance higher than in lake fish, and the presence of Salinicoccus, Marinobacter, and Marinobacterium genera exclusively in sea fish is likely due to the fact that these bacteria are halophilic, as previously reported (Chen et al, 2007;Durán-Viseras et al, 2021;Grimaud, 2010).…”
Section: Variation In the Composition Of Bacterial Community In Smoke...supporting
confidence: 73%
“…Important inter-individual variation in the composition of bacterial communities among fishes of the same species has also been previously reported (Arias et al, 2019;Boutin et al, 2014). The detection of the genus Photobacterium in sea fish with relative abundance higher than in lake fish, and the presence of Salinicoccus, Marinobacter, and Marinobacterium genera exclusively in sea fish is likely due to the fact that these bacteria are halophilic, as previously reported (Chen et al, 2007;Durán-Viseras et al, 2021;Grimaud, 2010).…”
Section: Variation In the Composition Of Bacterial Community In Smoke...supporting
confidence: 73%
“…In contrast, only two high-quality nirBD -carrying MAGs (i.e., MAG nos. 39 and 57) from Marinobacterium and Planctomycetaceae were likely the fermentative DNRA bacteria as they lacked most of the catalytic and regulatory genes related to ANR. , …”
Section: Resultsmentioning
confidence: 99%
“…39 and 57) from Marinobacterium and Planctomycetaceae were likely the fermentative DNRA bacteria as they lacked most of the catalytic and regulatory genes related to ANR. 79,80 The genomic loci within each of 37 nirBD-carrying MAGs were screened for nirBD and nasA in the same gene cluster as this is a genetic-level prerequisite for ANR. 73,74 Data revealed that 24 of 37 nirBD-carrying MAGs possessed a gene cluster containing nirBD and nasA together (Figure S2).…”
Section: Metagenomic and Metatranscriptomic Analysis Revealed The Pot...mentioning
confidence: 99%
“…Both classical culture techniques and metagenomic techniques have been used. The four research papers in this Special Issue are related to the study of biodiversity in different hypersaline environments [ 5 , 6 , 7 , 8 ].…”
mentioning
confidence: 99%